2020
DOI: 10.1155/2020/1682463
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Choroidal Vascularity Index in Keratoconus Patients Using Swept-Source Optical Coherence Tomography-Based Binarization Techniques

Abstract: Purpose. To analyse the vascular density of the choroid in a keratoconus (KC) population using swept-source optical coherence tomography (SS-OCT). Methods. Prospective, noninterventional study that analysed 97 eyes from 52 KC patients and 145 eyes from 89 healthy controls. The sample was divided in four different age groups. Inclusion criteria were topographic diagnosis of KC using Pentacam, axial length shorter than 26 mm, good quality of the images, and no other systemic or ocular diseases. A 12 mm horizonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 36 publications
1
32
1
Order By: Relevance
“…The median age was 24.00 years (range [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and individuals in our sample were predominately men (76.3%). Median best corrected visual acuity (BCVA) was 0.90 Snellen (range 0.10-1.00), with glasses or contact lenses.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The median age was 24.00 years (range [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and individuals in our sample were predominately men (76.3%). Median best corrected visual acuity (BCVA) was 0.90 Snellen (range 0.10-1.00), with glasses or contact lenses.…”
Section: Resultsmentioning
confidence: 86%
“…The recent findings of increased CT in KC patients raised the question of whether CT could help to differentiate progressive from non-progressive disease [23][24][25][26][27] . Until now all evaluations of KC progression were centered in tomographic and biomechanical corneal parameters 21,22,[28][29][30][31] , but the recently raised questions of an inflammatory hit in the disease and an increased CT in those patients opens new research possibilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 Furthermore, the same authors recently studied the exact components of the thicker choroid in KC and found that vascular region and corrected choroidal percentage of vascularity are also statistically increased in KC patients when compared with healthy controls. 31 If these findings are only an association without any role in the KC, or if they are part of a complex pathogenesis process is still unknown. The overall evidence and our results support the idea that inflammatory mechanisms could contribute both to KC activity and increase of CT, claiming a role for inflammation and potentially for atopy in its pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…OCT angiography (OCT-A) is a non-invasive imaging tool that allows detailed visualization of the retinal microvasculature to be obtained. Therefore, in this study, we compared the retinal vascularization and corneal parameters of patients with diagnosed KC with those of a control group using SS-OCT [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%